The Impact of Medication Anticholinergic Burden on Cognitive Performance in People With Schizophrenia. Issue 6 (December 2017) - Ang, Mei San; Abdul Rashid, Nur Amirah; Lam, Max; Rapisarda, Attilio; Kraus, Michael; Keefe, Richard S.E.; Lee, Jimmy
Abstract: Background: Cognitive deficits are prevalent in people with schizophrenia and associated with functional impairments. In addition to antipsychotics, pharmacotherapy in schizophrenia often includes other psychotropics, and some of these agents possess anticholinergic properties, which may impair cognition. The objective of this study was to explore the association between medication anticholinergic burden and cognition in schizophrenia. Methods: Seven hundred five individuals with schizophrenia completed a neuropsychological battery comprising Judgment of Line Orientation Test, Wechsler Abbreviated Scale of Intelligence Matrix Reasoning, Continuous Performance Test–Identical Pairs Version, and the Brief Assessment of Cognition in Schizophrenia. Cognitive g and 3 cognitive factor scores that include executive function, memory/fluency, and speed of processing/vigilance, which were derived from a previously published analysis, were entered as cognitive variables. Anticholinergic burden was computed using 2 anticholinergic scales: Anticholinergic Burden Scale and Anticholinergic Drug Scale. Duration and severity of illness, antipsychotic dose, smoking status, age, and sex were included as covariates. Results: Anticholinergic burden was associated with poorer cognitive performance in cognitive g, all 3 cognitive domains and most cognitive tasks in multivariate analyses. The associations were statistically significant, but the effect sizes were small (for Anticholinergic Burden Scale, Cohen f 2 = 0.008; for Anticholinergic Drug Scale, Cohen f 2 = 0.017). Conclusions: Although our results showed a statistically significant association between medications with anticholinergic properties and cognition in people with schizophrenia, the impact is of doubtful or minimal clinical significance.